2020
DOI: 10.3390/ijms21197037
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modifications of the Quinolin-4-yloxy Core to Obtain New Staphylococcus aureus NorA Inhibitors

Abstract: Tackling antimicrobial resistance (AMR) represents a social responsibility aimed at renewing the antimicrobial armamentarium and identifying novel therapeutical approaches. Among the possible strategies, efflux pumps inhibition offers the advantage to contrast the resistance against all drugs which can be extruded. Efflux pump inhibitors (EPIs) are molecules devoid of any antimicrobial activity, but synergizing with pumps-substrate antibiotics. Herein, we performed an in silico scaffold hopping approach starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The selected four cores, 1,7‐naphthyridine, 1,8‐naphthyridine, quinazoline and isoquinoline (Figure 3 A), generated five virtual hits ( 6 a–10 a – Table 1 ) since the quinazoline core characterized two regioisomeric virtual hits ( 8 a and 10 a – Figure 3 B), having 2‐phenylquinazoline and 4‐phenylquinazoline scaffolds, respectively. In addition to the five identified virtual hits ( 6 a–10 a ), a set of 5 close analogues having an ethylpiperidine chain in place of the ethyl‐ N , N ‐diethylamine was also designed (derivatives 6 b – 10 b – Table 1 ), taking advantage from the excellent results previously obtained with compounds 3 [34] and 4 [37] possessing this portion. However, during the synthesis of derivatives 7 a and 7 b , we only observed the formation of the respective N ‐alkylated regioisomers 11 a and 11 b (structures and fitness scores on ModB and ModC in Table 1 ) which, when analyzed by Phase on ModB and ModC, did not reach the threshold of fitness values we imposed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected four cores, 1,7‐naphthyridine, 1,8‐naphthyridine, quinazoline and isoquinoline (Figure 3 A), generated five virtual hits ( 6 a–10 a – Table 1 ) since the quinazoline core characterized two regioisomeric virtual hits ( 8 a and 10 a – Figure 3 B), having 2‐phenylquinazoline and 4‐phenylquinazoline scaffolds, respectively. In addition to the five identified virtual hits ( 6 a–10 a ), a set of 5 close analogues having an ethylpiperidine chain in place of the ethyl‐ N , N ‐diethylamine was also designed (derivatives 6 b – 10 b – Table 1 ), taking advantage from the excellent results previously obtained with compounds 3 [34] and 4 [37] possessing this portion. However, during the synthesis of derivatives 7 a and 7 b , we only observed the formation of the respective N ‐alkylated regioisomers 11 a and 11 b (structures and fitness scores on ModB and ModC in Table 1 ) which, when analyzed by Phase on ModB and ModC, did not reach the threshold of fitness values we imposed.…”
Section: Resultsmentioning
confidence: 99%
“…Data obtained in this work from the replacement of the quinoline with five different scaffolds will improve these models. Indeed, we observed that for retaining NorA inhibition activity: i ) an extended aromatic portion in the central scaffold is needed [34] with quinoline and quinazoline scaffolds preferred over 1,7‐naphthyridine and 1,8‐naphthyridine; ii ) nitrogen at 1‐position of the quinoline core is essential as demonstrated by the lack of activity of isoquinoline derivatives 9 a and 9 b ; iii) nitrogen at 3‐position (quinazoline analogues) can improve NorA EPI activity and in parallel reduce human cell toxicity. Therefore, these new findings will be used to build new updated pharmacophoric models that will be useful to perform drug repositioning studies and virtual screening campaigns to identify new NorA EPIs and also, as recently demonstrated, [45] novel nontuberculous mycobacteria efflux inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, with the aim to enrich the array of NorA EPIs, the same research group performed a scaffold-hopping approach of the quinoline core followed by a pharmacophore-based virtual screening [72,73]. Therefore, the quinoline-4-yloxy core of 20 (Figure 7) was replaced by several scaffolds arising from the smart fragmentation of approved drugs to generate a virtual library that was screened on two previously reported pharmacophore models for NorA EPIs [74].…”
Section: Quinoline Derivativesmentioning
confidence: 99%
“…The shift of the C-2 aryl moiety to the C-3 position afforded derivatives les potent as NorA EPIs, while improving NTM EPI activity (see below), similarly to wha happens for the position of the alkylamino chain if moved from the oxygen at C-4 to th N-1 position. Recently, with the aim to enrich the array of NorA EPIs, the same research group performed a scaffold-hopping approach of the quinoline core followed by a pharmacophorebased virtual screening [72,73]. Therefore, the quinoline-4-yloxy core of 20 (Figure 7) was replaced by several scaffolds arising from the smart fragmentation of approved drugs to generate a virtual library that was screened on two previously reported pharmacophore models for NorA EPIs [74].…”
Section: Quinoline Derivativesmentioning
confidence: 99%